Developmental Delay/Mental Retardation of Unknown Origin in Children: Genetic Analysis of 93 Cases - WANG Jing, LIU Yun, HUANG Haoyu, WU Jinting, LIU Chunming, ZHANG Yangping, WANG Wenjuan (Zhongguo quanke yixue, 2023)
Background It is hard to make an early and accurate diagnosis of developmental delay (DD) /mental retardation (MR) in children due to complex etiology, diverse and heterogeneous clinical manifestations of the disease. There are few large-sample analyses of the clinical and genetic test data of these children in China. Objective To perform an analysis of genetic test results of children with DD/MR, providing evidence for genetic diagnosis, treatment plan formulation and prognosis assessment in such children. Methods Ninety-three children with DD/MR of unknown origin were selected from Department of Rehabilitation, Kunming Children's Hospital from September 2017 to September 2021. Whole-exome sequencing (WES) was performed to explore pathogenic gene mutations associated with clinical manifestations. Copy number variation (CNV) detection was conducted to examine the characteristics of pathogenic CNVs. The detection of gene mutations was analyzed. Results The DD/MR in the children was mainly manifested by motor or global DD, or MR, and with a developmental level falling behind normal developmental milestones. Seventy-four cases (79.6%) were detected with genetic variants, and the detection rate was 79.6%, among whom 40 (43.0%) with pathogenic gene mutations, 13 (14.0%) with gene CNVs, and 21 (22.6%) with mutations of uncertain significance. The genetic test results involved more than 50 pathogenic genes in total. The most prevalent disease caused by gene mutation was spinal muscular atrophy caused by mutations in the SMN1 gene (10.0%, 4/40), followed by Bethlem myopathy-1 caused by mutations in the COL6A2 gene (7.5%, 3/40) and Joubert syndrome-21 caused by mutations in CSPP1 (5.0%, 2/40) . Conclusion Pathative gene mutations and gene copy number variants may be main causes of DD/MR. SMN1, COL6A2, and CSPP1 are common mutated genes in DD/MR patients. WES combined with CNV detection may greatly contribute to the exploration of the etiology of DD/MR, especially for DD/MR manifested by atypical phenotypes and clinical manifestations.